Medical image data processing method and device and storage medium - ZHU WANJING (2022)
The invention discloses a medical image data processing method and device and a storage medium. The method comprises the steps of collecting a skeleton image of a target person, uploading basic information of the target person, analyzing the basic information of the target person, analyzing skeleton similarity of the target person, analyzing skeleton lesion of the target person, analyzing a reference treatment scheme of the patient and generating a pathological report of the patient. If the target person is sick, the pathological report of the sick person is obtained through analysis, so that the efficiency of an attending doctor for analyzing a treatment scheme is improved to a certain extent, and when the similar skeleton image of the target person is screened out, the skeleton contour of the target person is compared with the skeleton contour of each patient; and the basic information of the target person and the basic information of each patient in the medical image database are analyzed, so that the reli